Enterococci in milk products : a dissertation presented in partial fulfilment of the requirements for the degree of Master of Veterinary Studies at Massey University, Palmerston North, New Zealand - Giménez-Pereira, Mirtha Lorena (Massey University, 2005)
This review examined the benefits and risks of enterococci in dairy products. Enterococci are ubiquitous bacteria present in the environment and in the gastrointestinal tract of healthy animals and humans. In milk products, they are used as probiotics resulting in positive effects on human digestibility. As adjunct starter cultures, enterococci release natural antimicrobial substances inhibiting adulteration due to food-borne pathogens. Thanks to the efficient utilisation of organic acids, enterococci contribute to the development of unique sensory characteristics in fermented dairy products. In contrast to these positive roles, some enterococcal strains were suspected to have pathogenic properties for humans, mainly based on specific virulence factors found in some strains of Enterococcus faecalis and to a lesser extent in strains of Enterococcus faecium. In addition, they were regarded as being resistant to several antibiotics. Since virulence factors and antibiotic resistance were found to be genetically encoded and transmissible, they may be transmitted to other enterococcal strains and even to other bacteria species. So far however, no genetic similarities and clear strain specificities have been observed among traits isolated from clinical or food sources. Thus, a pathogenic potential could only be associated with clinical strains, not food strains. Moreover, there is currently no evidence for pathogenic effects on humans. However, evidence for pathogenicity exists from three experimental models in animals. Due to the efficient removal of enterococci during processing, enterococci may be regarded as ‘contaminants’ if found in processed dairy foods.
Keywords: Enterococcus; Enterococcal infections; Dairy products